STRUKTUR, DIKSI, DAN KONJUNGSI TEKS PROSEDUR KARYA SISWA KELAS VII SMP NEGERI 1 KOTA SOLOK - Ulfa, Wildani; Rasyid, Yulianti (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT The research aims to describe generic structure and language features of procedure texts by seventh grade students in SMP Negeri 1 Kota Solok. The method that is used is descriptive qualitative method. The data of the research are procedure texts collected in many sources such as the documents of 32 text procedure written by the students. The instrument of this research is the researcher her self. Data were analyzed by describing, analyzing, and discussing the data toward the theory. Based on the results of the study, there are two things that can be concluded. First, the seventh grade students in SMP Negeri 1 Kota Solok have used the five generic structure of procedure text in writing. The generic structures of of procedure text are title, purpose, tool or meterial, and closing. It is proven by 32 procedure texts that have been analyzed, there are all texts have titles, tools, and materials, as well working steps, only 8 texts that have a purpose. Students have not been able to write a good closing in making the procedure text. This is evident from 32 texts analyzed only 6 texts that have a cover. Second, in terms of language. The happiness analyzed is three, namely diction, conjunction, and imperative sentences. Of the 32 research data found 4,099 the number of diction consisting of 3,949 standard diction and 150 diction which are not standard. From 32 research data found 436 number of conjunctions consisting of 420 uses of precision conjunctions and 16 improper conjunctions.  Kata Kunci: Struktur Teks, Diksi Teks, Konjungsi Teks